2021
DOI: 10.1590/s0104-12902021190276
|View full text |Cite
|
Sign up to set email alerts
|

Da Amazônia ao guia: os dilemas entre a alimentação quilombola e as recomendações do guia alimentar para a população brasileira

Abstract: Resumo O objetivo deste trabalho é analisar se o hábito alimentar das famílias quilombolas paraenses segue as orientações do Guia Alimentar para a População Brasileira, publicado pelo Ministério da Saúde, em 2014. Foram realizadas entrevistas semiestruturadas nas comunidades de Santo Antônio (Concórdia do Pará, nordeste paraense) e São João (Salvaterra, ilha do Marajó) sob o protocolo CEP 060/07. Foram feitas análises do consumo e das preferências alimentares de acordo com o guia. Os resultados evidenciam: alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although such other causes should be considered, hunting activities have been reported to be common among quilombola individuals, and such activities form a source of animal protein for remote communities in Brazil [ 34 ]. In such a scenario, the present study has corroborated with a study on hunting and ecology of mammals among quilombola individuals in southeastern Brazil revealed that the animals hunted were mostly small mammals such as white-lipped peccaries, coatis, armadillos, and opossums [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although such other causes should be considered, hunting activities have been reported to be common among quilombola individuals, and such activities form a source of animal protein for remote communities in Brazil [ 34 ]. In such a scenario, the present study has corroborated with a study on hunting and ecology of mammals among quilombola individuals in southeastern Brazil revealed that the animals hunted were mostly small mammals such as white-lipped peccaries, coatis, armadillos, and opossums [ 35 ].…”
Section: Discussionmentioning
confidence: 99%